Injection laryngoplasty during transoral laser microsurgery for early glottic cancer: a randomized controlled trial - Ayham Al Afif; Matthew H. Rigby; Colin MacKay; Timothy F. Brown; Timothy J. Phillips; Usman Khan; Jonathan R. B. Trites; Martin Corsten; S. Mark Taylor (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Transoral laser microsurgery is widely used for treating T1/T2 glottic cancers. Hyaluronic acid (HA) is commonly used in vocal cord augmentation. We investigated the impact of intra-operative injection laryngoplasty on voice outcomes in early glottic cancer. Methods Twenty patients were randomized to the treatment group receiving HA injection to the vocal cord contralateral to the lesion; or the control group, receiving no injection. Patients had a Voice Handicap Index-10 (VHI-10) questionnaire and a Maximum Phonation Time (MPT) measurement preoperatively and at 3, 12 and 24 months post-operatively. Mean change in VHI-10 and MPT, compared to baseline and between time points, were compared. Survival estimates were calculated. Results Mean VHI-10 scores improved over time amongst all patients. There were no changes in mean VHI-10 from pre-operative values to 3, 12 or 24 months post-operatively. There were no significant differences when comparing various timepoints between groups. There were no significant changes in MPT amongst the groups, or the time-points compared. Two-year overall survival was 91.7%; disease free survival was 80.9%; no difference in recurrence free survival was seen between the groups. Conclusion Subjective voice scores improved over time in both groups; there were no improvements in VHI-10 or MPT scores in the injection group, over control, at any time points. We saw no significant impact for intra-operative HA injection laryngoplasty on subjective or objective voice outcomes following surgery for early glottic cancers. Graphical abstract